Sleep‐wake abnormalities in patients with cirrhosis. Issue 2 (23rd December 2013) - Montagnese, Sara; De Pittà, Cristiano; De Rui, Michele; Corrias, Michela; Turco, Matteo; Merkel, Carlo; Amodio, Piero; Costa, Rodolfo; Skene, Debra J.; Gatta, Angelo
<x xml:space="preserve">Abstract</x> A considerable proportion of patients with cirrhosis exhibit insomnia, delayed sleep habits, and excessive daytime sleepiness. These have been variously attributed to hepatic encephalopathy and impaired hepatic melatonin metabolism, but the understanding of their pathophysiology remains limited and their treatment problematic. Sleep is regulated by the interaction of a homeostatic and a circadian process. The homeostatic process determines sleep propensity in relation to sleep‐wake history, thus the need to sleep increases with the duration of the waking period. The circadian process, which is marked by the 24‐hour rhythm of the hormone melatonin, is responsible for the alternation of high/low sleep propensity in relation to dark/light cues. Circadian sleep regulation has been studied in some depth in patients with cirrhosis, who show delays in the 24‐hour melatonin rhythm, most likely in relation to reduced sensitivity to light cues. However, while melatonin abnormalities are associated with delayed sleep habits, they do not seem to offer a comprehensive explanation to the insomnia exhibited by these patients. Fewer data are available on homeostatic sleep control: it has been recently hypothesized that patients with cirrhosis and hepatic encephalopathy might be unable, due to excessive daytime sleepiness, to accumulate the need/ability to produce restorative sleep. This review will describe in some detail the features of sleep‐wake disturbances in patients with cirrhosis, their mutual relationships, and those, if any, with hepatic failure/hepatic encephalopathy. A separate section will cover the available information on their pathophysiology. Finally, etiological treatment will be briefly discussed. (Hepatology 2014;59:705–712)